Outcomes of Diabetes Care Intervention on Knowledge and Practice of Self-care in Some Rural and Urban Healthcare Facilities, Edo State - Osarenmwinda, Monday Ikponmwosa; Erah, Patrick Omonua (Indian Journal of Pharmacy Practice)
Background: Diabetes Mellitus (DM) is on the increase in Nigeria; consequently, there is a need to promote self-care practices among all patients. The study aimed to evaluate outcomes of diabetes care intervention on knowledge and practice of self-care among diabetes patients in rural and urban healthcare facilities in Edo State. Materials and Methods: In a descriptive cross-sectional, data on knowledge and practice of self care among Diabetes patients were collected using self-developed and Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. Analysis was both descriptive and inferential. Paired t-test was performed to compare the results from diabetes patients from General Hospital (GH), Abudu and Specialist Hospital (SH), Benin, and results were considered significant with P<0.05. Results: There was a significant difference (P<0.05) in the knowledge of self-care among patients. Diabetes patients in specialist hospital, Benin had a better knowledge of self-care (mean score >3) than those in general hospital, Abudu. Diabetes patients from general hospital, Abudu (rural) comply more with a mean practice of diabetes self-care in general exercise (5.58±1.42) and specific exercises (5.44±0.98). Diabetes patients from specialist hospital, Benin test their blood sugars themselves and the number of times recommended. After 6 months of educational intervention on diabetes care, knowledge and practice of diabetes self care improved significantly (p<0.05) across the various domains, but with better performance in specialist hospital, Benin. Conclusion: The study justifies a low quality of diabetes care delivery in both rural and urban health care facilities and significantly improved with educational interventions.
Keywords: Diabetes; Prevalence; Self-care; Knowledge; Practice